Clinical significance of left ventricular reverse remodeling after catheter ablation of atrial fibrillation in patients with left ventricular systolic dysfunction. Issue 5 (May 2021) - Okada, Masato; Tanaka, Nobuaki; Oka, Takafumi; Tanaka, Koji; Ninomiya, Yuichi; Hirao, Yuko; Yoshimoto, Issei; Inoue, Hiroyuki; Kitagaki, Ryo; Onishi, Toshinari; Koyama, Yasushi; Okamura, Atsunori; et al.
Highlights: Left ventricular reverse remodeling (LVRR) after atrial fibrillation (AF) ablation is common in patients with left ventricular systolic dysfunction. LVRR was predicted by non-paroxysmal AF without apparent structural heart disease. Recurrence as persistent AF was associated with LVRR but paroxysmal AF was not. Patients with LVRR experienced less heart failure hospitalizations and cardiovascular deaths. Abstract: Background: Left ventricular (LV) reverse remodeling (LVRR) after catheter ablation of atrial fibrillation (AFCA) has not been fully described. This study investigated the predictors and clinical outcomes of LVRR after AFCA in patients with LV systolic dysfunction. Methods: Of 3319 consecutive patients who underwent first-time AFCA between January 2012 and October 2019, 376 with a baseline LV ejection fraction of <50% were retrospectively evaluated. They were subjected to 256-slice multidetector computed tomography (MDCT) scanning at baseline and 3 months after AFCA. The LVRR was defined as a decrease in the LV end-systolic volume of ≥15%. Results: The prevalence of LVRR was 83% ( n = 306). Multivariate logistic regression analysis including age, body mass index, diabetic status, beta-blocker use, and LV diastolic diameter revealed that the predictors of LVRR were non-paroxysmal atrial fibrillation (AF) (odds ratio, 2.68; 95% confidence interval, 1.42–5.05; p = 0.002) and absence of apparent underlying structural heart disease (4.81; 2.31–10.0; p <0.001). The prevalence of LVRR differed depending on AF recurrence pattern prior to the post-MDCT [no episode vs. paroxysmal episode (lasting <7 days) vs. persistent episode (lasting ≥7 days), 84% vs. 81% vs. 63%, respectively, p = 0.023]. During a median follow-up of 32 months, the incidence of paroxysmal form of AF recurrence was similar, whereas persistent form of AF recurrence was less frequent in patients with LVRR (10.5% vs. 18.6%, p = 0.018). Heart failure hospitalizations (2.3% vs. 15.7%, p <0.001), cardiovascular deaths (0.7% vs. 4.3%, p = 0.015), and all-cause deaths (1.3% vs. 5.7%, p = 0.018) were similarly less frequent in those with LVRR. Conclusions: LVRR after AFCA, which was predicted by non-paroxysmal AF without any apparent structural heart disease at baseline, was associated with persistent form of AF recurrence prior to the evaluation. LVRR was associated with favorable clinical outcomes. Graphical abstract: Image, graphical abstract